2012
DOI: 10.3389/fimmu.2012.00079
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TLR2 in Infection and Immunity

Abstract: Toll-like receptors (TLRs) are recognition molecules for multiple pathogens, including bacteria, viruses, fungi, and parasites. TLR2 forms heterodimers with TLR1 and TLR6, which is the initial step in a cascade of events leading to significant innate immune responses, development of adaptive immunity to pathogens and protection from immune sequelae related to infection with these pathogens. This review will discuss the current status of TLR2 mediated immune responses by recognition of pathogen-associated molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
520
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 600 publications
(581 citation statements)
references
References 238 publications
2
520
1
5
Order By: Relevance
“…TLR2/TLR1 and TLR2/TLR6 recognize triacylated lipoproteins and diacylated lipoproteins, respectively, and induce the production of various proinflammatory cytokines, but not type I IFNs. The crystal structures of the two heterodimers revealed that each heterodimer forms an "m"-shaped complex with its ligand, thereby stabilizing the two receptors (Jin et al 2007;Oliveira-Nascimento et al 2012). A recent study showed the existence of TLR2/ TLR10 preformed dimers, although their function is unknown (Guan et al 2010).…”
Section: Microbial Sensing By Tlrsmentioning
confidence: 99%
“…TLR2/TLR1 and TLR2/TLR6 recognize triacylated lipoproteins and diacylated lipoproteins, respectively, and induce the production of various proinflammatory cytokines, but not type I IFNs. The crystal structures of the two heterodimers revealed that each heterodimer forms an "m"-shaped complex with its ligand, thereby stabilizing the two receptors (Jin et al 2007;Oliveira-Nascimento et al 2012). A recent study showed the existence of TLR2/ TLR10 preformed dimers, although their function is unknown (Guan et al 2010).…”
Section: Microbial Sensing By Tlrsmentioning
confidence: 99%
“…In both of the sets subjected to MD simulations, the N ‐terminal and C ‐terminal regions showed higher fluctuation than other LRR regions. The TLR2 subfamily binds with a wide‐range of microbial compounds and proteins in addition to lipoproteins and lipopeptides 25. Among them, peptidoglycan of Staphylococcus aureus can bind to the N ‐terminus or C ‐terminus of the TLR2 42; proline‐proline‐glutamic acid 18 of Mycobacterium tuberculosis has been shown to interact with the C ‐terminal region of TLR2 43; and both the N ‐ and C ‐terminus LRRs of TLR1 and TLR6 play a minimal role in accommodating LT‐IIb‐B 5 44.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of PRRs and the corresponding PAMPs can induce the release of activation signals and trigger the synthesis and secretion of cytokines and co-stimulatory molecules necessary for the initiation of adaptive immune responses. TLRs usually recognize and bind with ligands such as lipopolysaccharide (LPS) [13], zymosan [14,15], Neospora caninum [16] and then induce APCs activation and Th1 programming during infection [17]. Among all TLRs, TLR-2 plays a significant role in macrophages activation and works as homodimer [18] or heterodimer with TLR1 or TLR6 [19] to recognize diverse PMAPs.…”
Section: Discussionmentioning
confidence: 99%
“…TLRs usually recognize and bind with ligands such as lipopolysaccharide (LPS) [13], zymosan [14,15], Neospora caninum [16] and then induce APCs activation and Th1 programming during infection [17]. Among all TLRs, TLR-2 plays a significant role in macrophages activation and works as homodimer [18] or heterodimer with TLR1 or TLR6 [19] to recognize diverse PMAPs. A cascade of events occurs after PAMP recognition by TLR-2, which activate host defense mechanisms and initiate an adaptive immune response in MyD88-dependent signaling pathway [20].…”
Section: Discussionmentioning
confidence: 99%